The doctor’s dilemma againts the patient’s right to information in clinical trial - Yusof, Yuhanif; Che Ngah, Anisah; Abdullah, Nor Anita; Megat Latif, Hairuddin; Md Desa, Md Rejab (International Academic Research Journal, 2015)
In clinical trials, the right to information has been recognized as a right of the patients.This is because the risks to the patients as subjects are inevitable.Therefore, the information about risks is important to disclose so that the patient can decide voluntarily whether to accept or reject the doctor‟s invitation to participate.However, the doctors‟ good intention to help the patients by inviting them to participate is questionable as risks are something uncertain until the trials are completed.Hence, the objective of this paper is to discuss on doctors‟ dilemma to disclose information on risks and the patients ‟right to get information.A qualitative methodology is used in writing this conceptual paper.The findings reveal that doctors must disclose information on risks to patients as risks can be evaluated. However, detail information on how the risks will occur need not be disclosed.The doctors‟ should not recruit patients as subjects if unable to bear responsibility to disclose information during the informed consent process.The usage of audio visual player on how the trial will be conducted is to recorded and aired to the patients to help them decide in participating in the trials is also proposed.